Bacteriology of Bronchial Aspirates in Patients with Endotracheal Intubation and Mechanical Ventilation - Rusepno Hasan; Mintardaningsih Mintardaningsih; Usman Warsa; Tertia Hutabarat (Paediatrica Indonesiana, 1983)
On 30 patients with endotracheal tubes and mechanical ventilation, bacteriological culture has been done using a simple, safe and quite reliable technique. During this study we found that gram negative bacteria especially Pseudomonas aeruginosa were the most frequent bacteria isolated. Other bacteria found were staphylococcus, pseudomonas species and Klebsiella pneumoniae. Based on sensitivity tests, the aminoglycoside especially amikacin is the recommended antibiotic against gram negative bacteria. As for gram positive bacteria, subenicilin, cloxacillin and cotrimoxazole are the potent antibiotics. The data presented in this study dearly support the usefulness and reliability of the technique.